Treatment of Developmental Dysplasia of Hip With Tubingen Hip Flexion Splint. Issue 5 (July 2015) - Pavone, Vito; Testa, Gianluca; Riccioli, Maria; Evola, Francesco R.; Avondo, Sergio; Sessa, Giuseppe
Abstract : Background: Developmental dysplasia of the hip is an anomaly of the hip joint. In patients with early diagnosis, within 3 to 6 months of life, the treatment is essentially conservative and involves the use of dynamic harness. The indication for the use of the Tubingen hip flexion splint is a dysplastic hip. The aim of this study is to report the experience of the Orthopaedic Clinic of the "University of Catania" regarding conservative treatment with the Tubingen harness of dysplastic hips diagnosed in children within 3 months of life. Methods: From January 1997 to July 2012, 5137 infants (10, 274 hips) aged within 3 months of life were submitted to ultrasonographic hip assessment. Start, duration of treatment, and outcome were investigated. Results: A total of 351 (6.83%) patients affected by developmental dysplasia of the hip for a total of 544 dysplastic hips (5.3%) were treated with the Tubingen hip flexion splint. Treatment was started on average 39 days of life. Harness were dressed for 24 hours a day and applied for a mean of 3.8 months. Mean follow-up was 6.4 years (range, 2.2 to 14 y). We obtained the following results: 482 (90.44%) dysplastic, unstable, or dislocated hips were successfully converted into type I hips with an α-angle of >64 degrees in the splint. Complications were reported in 3 (0.55%) hips. No statistically significant relationship was found between the duration of therapy and the time when treatment was started, early or late within the first week of life ( P =0.152). Conclusions: Dysplastic, unstable, and dislocated hips can be successfully treated with the Tubingen hip flexion splint, reporting good clinical and ultrasonographic outcomes.